Influence of Graft Bending Angle on Femoral Tunnel Widening After Double-Bundle ACL Reconstruction: Comparison of Transportal and Outside-In Techniques. Issue 10 (21st October 2021) - Lee, Do Kyung; Kim, Jun Ho; Lee, Byung Hoon; Kim, Hyeonsoo; Jang, Min Jae; Lee, Sung-Sahn; Wang, Joon Ho
Background: Previous studies have suggested that increased mechanical stress due to acute graft bending angle (GBA) is associated with tunnel widening and graft failure after anterior cruciate ligament (ACL) reconstruction. Few studies have compared the GBA between the outside-in (OI) and the transportal (TP) techniques. Purpose: To evaluate the influence of GBA on clinical outcomes and tunnel widening after ACL reconstruction with OI versus TP technique. Study Design: Cohort study; Level of evidence, 3. Methods: Included in the study were 56 patients who underwent double-bundle ACL reconstruction (n = 28 in the OI group and n = 28 in the TP group). Clinical outcomes (Lysholm, International Knee Documentation Committee, Tegner score, and knee laxity) 1 year postoperatively were evaluated. Computed tomography scans at 5 days and 1 year postoperatively were used for imaging measurements, and the femoral tunnel was divided into the proximal third, middle, and aperture sections. The GBA and cross-sectional area (CSA) were measured using image analysis software and were compared between groups. A correlation analysis was performed to determine if the GBA affected clinical outcomes or tunnel widening. Results: No significant difference was observed in clinical outcomes between the groups. The GBA of both the anteromedial (AM) and posterolateral bundles were more acute in the OI group compared with the TP group ( P < .05). The CSA at the AM tunnel aperture increased significantly in the OI group (84.2% ± 64.3%) compared with the TP group (51.4% ± 36.7%) ( P = .04). However, there were no differences in the other sections. In the Pearson correlation test, GBA was not correlated with tunnel widening or clinical outcomes. Conclusion: Regardless of technique, the GBA did not have a significant influence on tunnel widening or clinical outcomes. Considering a wider AM tunnel aperture, a more proximal and posterior AM tunnel position might be appropriate with the OI technique.